Maybe this time - Crusie, Jennifer (St. Martin's Press, 2010)
North Archer, Andie Miller's ex-husband, asks her to become the guardian of two orphans who have driven out three nannies already--and live in a haunted house! What follows is a hilarious adventure in exorcism, including a self-doubting parapsychologist, an annoyed medium, her Tarot-card reading mother, an avenging ex-mother-in-law, and, of course, her jealous fiancé. Just when Andie thinks things couldn't get more complicated, North shows up on the doorstep making her wonder if "maybe this time" things could be different between them.